Historical vignettes, 2nd series - Capes, Bernard, 1854-1918 (Salt Lake City, UT : Project Gutenberg, 2023)
"Historical Vignettes, 2nd Series" by Bernard Capes is a historical account written in the early 20th century. This collection features a series of historical sketches, each portraying notable figures and events from various periods in history, such as "Dead Man$1 (Bs Plack," "Fair Rosamond," and "Maid Marian." The vignettes explore themes of love, ambition, and treachery, drawing from rich historical contexts to bring characters like Elfrida and Eleanor of Aquitaine to life. At the start of "Historical Vignettes, 2nd Series," the reader is introduced to the character Elfrida, who is depicted as a beautiful young wife caught in a web of love and jealousy involving her husband, Athelwold, and the King. As the story unfolds, Elfrida grapples with her husband's deep-seated fears surrounding their relationship, leading to potential conflict as the King is set to make an unexpected visit. Complications arise when Elfrida is urged to deceive the King to protect her husband from his wrath, showcasing the intricate interplay of love, loyalty, and treachery in the face of political intrigue. The narrative often shifts perspectives, providing a diverse portrayal of historical dynamics, setting the stage for the unfolding drama. (This is an automatically generated summary.)s
"Dead man's plack" -- Fair Rosamond -- Maid Marian -- Raleigh -- Marlowe -- Queen Elizabeth -- Drake's chaplain -- George Buchanan -- The Lord Treasurer -- The Princess Elizabeth -- James II -- The King's Champion -- George I -- George III -- The hero of Waterloo -- Beau Brummell -- Paganini -- Napoleon -- Leonardo da Vinci -- Wu Taotsz, the celestial painter -- Cleopatra and the Decurion -- The Galilean.
"Ten of the following sketches are reprints from a volume, Historical Vignettes [1st series, #70642], published by Mr. Fisher Unwin in 1910. The remaining twelve here appear in book-form for the first time."--Note.
Release date is 2023-05-01
an anonymous Project Gutenberg volunteer
Keywords: Historical fiction; Short stories, English